2018
DOI: 10.1111/adj.12627
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and dental morbidity in long‐term allogeneic blood and marrow transplant survivors in Australia

Abstract: Despite oral complications commonly occurring after Allo-BMT, many survivors receive inadequate dental care. These results emphasize the need for improved oral health education, the importance of regular dental checks and improvement in the delivery of dental health services for BMT survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 45 publications
1
22
0
2
Order By: Relevance
“…In one study among HSCT recipients, patients with extensive cGVHD had on average worse QoL, compared to patients with limited or without cGVHD [34]. In another study among HSCT recipients, of which 33.3% suffered from cGVHD, a reduced QoL was found [35]. Another study reported that the QoL correlated with oral mucositis due to HSCT [36].…”
Section: Discussionmentioning
confidence: 98%
“…In one study among HSCT recipients, patients with extensive cGVHD had on average worse QoL, compared to patients with limited or without cGVHD [34]. In another study among HSCT recipients, of which 33.3% suffered from cGVHD, a reduced QoL was found [35]. Another study reported that the QoL correlated with oral mucositis due to HSCT [36].…”
Section: Discussionmentioning
confidence: 98%
“…One cohort study did not report on the follow-up time (Lopez Lopez et al, 2000). The mean/median follow-up time in five cross-sectional studies ranged from 339 days to 7 years (Baker et al, 2004;Brand et al, 2009;Dyer et al, 2018;Fantozzi et al, 2020;Osiak et al, 2018). In one cross-sectional study,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Gross dental caries, defined as caries clinically affecting at least half of the tooth surfaces, was found in 8% of allogeneic HSCT survivors (Fantozzi et al, 2020). In cross-sectional surveys, 37% of the HSCT survivors reported dental caries (Dyer et al, 2018), and 19% reported an increased dental caries rate (Hull et al, 2012). The highest prevalence was reported in a cohort study at high risk of bias, in which 43% of the HSCT recipients showed caries 3 months after transplantation, in accordance with the proportion of patients displaying caries before HSCT (Barrach et al, 2015).…”
Section: Dental Cariesmentioning
confidence: 99%
“…Tooth decay, or dental caries, is a common finding in survivors of HSCT [Elad et al, 2015]. A high caries prevalence was reported in patients who had undergone allogeneic HSCT 1-14 years previously, in comparison with the general population [Dyer et al, 2018]. HSCT recipients may already be at higher caries risk before the treatment, as patients planned for HSCT were reported to have higher number of decayed, missing, and filled teeth (DMFT), compared with the general population [Mauramo et al, 2019] or with healthy controls [Uutela et al, 2019b[Uutela et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%